2019
DOI: 10.18502/ijrm.v17i10.5494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamin D status, parathyroid hormone, and calcium among Iranian pregnant women with preeclampsia: A case-control study

Abstract: Background: Preeclampsia is considered as a serious life-threatening condition that could affect both maternal and fetal outcome. Many studies have examined the association of nutritional factors with the incidence of preeclampsia. However, little is known about the possible role of vitamin D in the development of preeclampsia among the Iranian population. Objective: The aim of the present study was to evaluate the association between vitamin D status and preeclampsia. Materials and Methods: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…In addition, the study showed that there was a statistically significant difference in the mean of Vitamin D level of mothers with full term pregnancy and preterm pregnancy. These results about the associations between neonatal and maternal Vitamin D, and neonatal weights and neonatal Vitamin D indicate the role of maternal Vitamin D in the growth of fetus and is consistent with results of many studies (10)(11)(12)(13)(14)31). Vitamin D levels in umbilical cord blood were nearly always higher compared to the levels in maternal blood; this is consistent with results of a study about factors associated with the prevalence of hypovitaminosis D in pregnant women and their neonates, and the high Vitamin D levels found in umbilical cord blood could be due to a positive maternal-foetal gradient or to placental synthesis of vitamin D. This protective mechanism would guarantee adequate vitamin D levels in the fetus and neonate during a period of rapid growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the study showed that there was a statistically significant difference in the mean of Vitamin D level of mothers with full term pregnancy and preterm pregnancy. These results about the associations between neonatal and maternal Vitamin D, and neonatal weights and neonatal Vitamin D indicate the role of maternal Vitamin D in the growth of fetus and is consistent with results of many studies (10)(11)(12)(13)(14)31). Vitamin D levels in umbilical cord blood were nearly always higher compared to the levels in maternal blood; this is consistent with results of a study about factors associated with the prevalence of hypovitaminosis D in pregnant women and their neonates, and the high Vitamin D levels found in umbilical cord blood could be due to a positive maternal-foetal gradient or to placental synthesis of vitamin D. This protective mechanism would guarantee adequate vitamin D levels in the fetus and neonate during a period of rapid growth.…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D deficiency/ insufficiency is associated with a number of adverse health outcomes that affect all age groups in both sexes (8,9) especially pregnant women and their neonates where several studies have highlighted that women are at high risk for vitamin D deficiency, and this is associated with adverse pregnancy outcomes, including preeclampsia, gestational diabetes and preterm delivery (10)(11)(12)(13)(14). A study in China showed that 34.8% of pregnant women were vitamin D deficient and 43.0% were vitamin D insufficient (15).…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Hamedanyan et al In 2019, 60 pregnant women with preeclampsia and 60 normal pregnant women were compared in terms of vitamin d, calcium, parathyroid hormone and phosphorus. Only vitamin d level was found to be significantly lower in the pregnant group with preeclampsia, but no relationship was observed between vitamin d status and the risk of developing preeclampsia [20] In our study, no significant relationship was found between normotensive pregnant women and 25hydroxyvitamin D levels and the development of preeclampsia.…”
Section: Discussioncontrasting
confidence: 83%
“…It was observed that hypocalcaemia may enhance the risk of preeclampsia more than 8-fold [14]. In contrast to the positive association, certain other studies did not report an association between calcium levels and preeclampsia [15][16][17][18], that may be due to differences in the study design, analytical techniques and different population and socio-economic conditions.…”
Section: Discussionmentioning
confidence: 97%